2015
DOI: 10.1007/s11136-015-1012-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term health-related quality of life for patients with Hirschsprung’s disease at 5 years after transanal endorectal pull-through operation

Abstract: Transanal pull-through operation disease showed a good postoperative long-term HRQoL. Overflow incontinence and age at time of surgery had a significant negative effect on all the aspects of children's HRQoL. Parental satisfaction was good and could be improved by more family inclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Though Mills et al found that girls with Hirschsprung's disease had higher scores across all HRQol scales, the difference was not signi cant(P<0.05) [33]. Many previous studies also indicated that gender did not have a signi cant effect on aspects of the global HRQol in children with Hirschsprung's disease [8,37,45]. Children whose household registration place was in Hangzhou got signi cantly higher scores than in other cities, which was highly likely that Hangzhou is the capital city with the highest GDP per capita which represent a higher level of socioeconomic status that means children there have access to better health services and education and develop positive coping mechanisms to management the adversities.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Though Mills et al found that girls with Hirschsprung's disease had higher scores across all HRQol scales, the difference was not signi cant(P<0.05) [33]. Many previous studies also indicated that gender did not have a signi cant effect on aspects of the global HRQol in children with Hirschsprung's disease [8,37,45]. Children whose household registration place was in Hangzhou got signi cantly higher scores than in other cities, which was highly likely that Hangzhou is the capital city with the highest GDP per capita which represent a higher level of socioeconomic status that means children there have access to better health services and education and develop positive coping mechanisms to management the adversities.…”
Section: Discussionmentioning
confidence: 93%
“…Roodbol et al reported that many children were held back in class or dropped out of school after developing Guillain-Barré syndrome [44]. Khalil found that age at time of surgery was negatively affecting school functioning (ß =-0.907) in children with Hirschsprung's disease [45].…”
Section: Discussionmentioning
confidence: 99%
“…Minus (-) sign indicates a negative impact. 15,29,34 À Psychosocial HrQoL worsens in adolescence, although physical morbidity improves 26,28,35 Gender þ No effect 13,32,33,39,40 þ Comparable HrQoL in infancy for boys and girls 38 À Reduced HrQoL in females from adolescence 34,37,38…”
Section: No Datamentioning
confidence: 99%
“…In contrast, others could not find a significant effect of sex on HrQoL, neither in younger nor older ages. 13,32,33,39,40 Thus, the impact of sex/gender on HrQoL in ARM/HD remains a matter of debate.…”
Section: Gendermentioning
confidence: 99%
See 1 more Smart Citation